DATA PRIVACY AND SECURITY PROTECTION STRATEGIES IN LIBRARY ELECTRONIC RESOURCES MANAGEMENT - Dahlian Persadha, Pratama; Judijanto, Loso; Susanti, Melly; Kreshna Reza, Heru (PT. Banjarese Pacific Indonesia, 2024)
Security is a crucial aspect in the digital age, especially in the management and protection of information. As the volume of information processed increases, the need to organize knowledge and provide adequate security becomes more pressing. This research emphasizes the importance of cybersecurity in the context of digital libraries, which must comply with certain technological and regulatory standards to protect user data and guarantee privacy when accessing electronic resources. Libraries face various challenges in protecting personal data on their electronic resources. This research addresses topics such as user privacy, data encryption, access management, and compliance with privacy laws. By addressing these issues comprehensively, libraries can ensure the protection of user privacy while optimizing the benefits of digital resources in today's information environment. The October 2023 cyberattack by a hacker group known as Rhysida on the British Library's internet information system emphasizes the importance of cybersecurity and data privacy for digital libraries. This research aims to provide insights and solutions to address these challenges, ensuring digital libraries can operate securely and efficiently.